Asymmetric synthesis with sulfur(IV) and sulfur(VI) - Liffey, Ryan Michael (2018)
This thesis reports findings in two projects utilising sulfur as a chiral auxiliary in asymmetric synthesis. The first section describes the enantioselective synthesis of isomeric harmonine in 8 steps with a 21% overall yield highlighting sulfinimine chemistry to selectively install the necessary chirality at the amine in the C-17 position. Ring closing metathesis was used to install the internal olefin which led to an inseparable mixture of geometric isomers. Further efforts were made towards the selective installation of the desired Z alkene. Two approaches are discussed, the first using alkyne metathesis as a key step with the second using alkenyl silanes in metathesis. The second section provides a discussion on the novel rearrangement of 2-vinylaziridine-2-carboxylates, derived from enantiopure sulfinimines, to unprecedented chiral cyclic sulfoximines. The synthesis of substituted cyclic sulfoximines has been achieved in one pot with high yields and complete stereocontrol. The mild conditions utilised allows access to a plethora of novel sulfoximine containing heterocycles in only three steps from commercially available aldehydes. A mechanistic hypothesis for the key rearrangement step is also proposed. Further functionalisation of these novel compounds provided access to a group of interesting cyclic sulfinamides in one pot using a catalytic amount of Zn(OTf)2. The formal synthesis of trachelanthamidine via the direct transformation a cyclic sulfoximine into a pyrroline is also disclosed, highlighting the use of these novel species in targeted synthesis.